Morphometric relations for Araucaria angustifolia (Bertol.) Kuntze in Santa Catarina, Brazil Relações morfométricas para Araucaria Angustifolia (Bertol.) Kuntze Em Santa Catarina - Klein D.R.* (2017)
Knowing the morphometry of a species and describing its relations help us in the planning and in the sustainable use of the forest. The objective of this study was to analyze morphometric relationships in order to fit models representing 121 Araucaria angustifolia trees sampled at two sites in São José do Cerrito, Planalto Catarinense. The measures were: diameter at breast height (Dap), height (h), crown insertion height (hic), crown radius (rc), crown length (cc), crown diameter (dc), slenderness index (IS), degree of slenderness (GE), formal cup (HR), crown ratio (Pc%) and sociological position (PS) of each individual. Person correlation was used to evaluate the relationships between morphometric variables. The covariance analysis was used to verify difference of level and slope in the adjustments of the models for the sites. The fit of the models was done by generalized linear models (MLG) in the gamma and normal distribution fields, identity and logarithmic link function for correlations greater than or equal to 0.7. The covariance analysis showed differences in the relations for each site, indicating the adjustment of different equations. The equations showed variations in morphometric relationships due to the shape-dimension change of each tree. The results show the modification in the shape of the canopy, from the social position of each tree, besides the diametrical influence and the space occupied by each tree in the forest, competition and site conditions. The established morphometric relationships were important to explain the growth dynamics of the species and the application of silvicultural interventions.